2014
DOI: 10.20533/iji.1742.4712.2014.0113
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Affecting End-user Performance of Information Systems

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
(115 reference statements)
3
4
0
Order By: Relevance
“…Thus, increasing IS usefulness. The study finding concurs with Abugabah and Sanzogni (2014) who established that the advantages got from the utilization of an IS vary from one user to another based on their characteristics thus the effects of the IS on user performance will differ in with regard to user type and usage, experience, position, age and gender. Similarly, Arning and Ziefle (2007) revealed that user traits, frequently referred to as "individual differences," make up the significant factors in explaining the effect and the usage of IS.…”
Section: User Characteristicssupporting
confidence: 88%
See 4 more Smart Citations
“…Thus, increasing IS usefulness. The study finding concurs with Abugabah and Sanzogni (2014) who established that the advantages got from the utilization of an IS vary from one user to another based on their characteristics thus the effects of the IS on user performance will differ in with regard to user type and usage, experience, position, age and gender. Similarly, Arning and Ziefle (2007) revealed that user traits, frequently referred to as "individual differences," make up the significant factors in explaining the effect and the usage of IS.…”
Section: User Characteristicssupporting
confidence: 88%
“…Consistency, validity and integrity of the information makes the users to have faith in the system and hence rely more on the IS in performing their tasks hence improving their performance. The study finding concurs with the views of Abugabah and Sanzogni (2014) who established that if critical operations that result in more accurate, accessible, comprehensive, relevant, and timely information are enabled, IS can improve performance indefinitely. Laudon and Laudon (2011) also observed that the same attributes of IQ that affect decision making.…”
Section: Statementsupporting
confidence: 87%
See 3 more Smart Citations